The role of insulin resistance and metabolic risk factors on culprit coronary plaque. (1st July 2015) - Park, Yae Min; Han, Seung Hwan; Seo, Jong Goo; Lee, Sihoon; Oh, Pyung Chun; Koh, Kwang Kon; Lee, Kyounghoon; Suh, Soon Yong; Kang, Woong Chol; Ahn, Taehoon; Choi, In Suck; Shin, Eak Kyun
Abstract: Background: Detailed relationships between insulin resistance (IR) and vulnerable plaque are not clear, therefore, we sought the role of IR and metabolic risk factors on culprit coronary plaque. Methods: Plaque components at a region of interest (ROI, 10 mm) were analyzed by virtual histology intravascular ultrasound. IR was defined as quantitative insulin sensitivity check index (QUICKI) ≤ 0.33. Seven metabolic risk factors (5 risk factors for metabolic syndrome defined by ATP III, history of smoking, and hsCRP) for IR were determined. Results: The data for 150 (males 104) patients were analyzed. Patients with IR (n = 69) had greater necrotic core (NC) at the ROI (21.2 ± 15.8 mm 3 vs 15.7 ± 11.9 mm 3, p = 0.02) than in patients without IR (n = 81). The NC at the ROI was correlated with QUICKI (r = − 0.16, p = 0.05), HbA1c (r = 0.24, p < 0.01), body mass index (r = 0.17, p = 0.04), presence of diabetes mellitus (r = 0.29, p < 0.001), hsCRP (r = 0.17, p = 0.04) and the numbers of risk factors for IR (r = 0.41, p < 0.001). The multivariate analysis revealed that the numbers of risk factors for IR was an independent factor for the NC at the ROI (beta coefficient = 0.44, p = 0.003), but QUICKI was not (beta coefficient = − 0.01, p = 0.94). Conclusions: Instead of a single measurement of IR index or each metabolic risk factor, clustering of risk factors for IR plays an important role on plaque vulnerability. Condensed abstract: We investigated the role of insulin resistance (IR) on culprit coronary plaque. Patients with IR had a greater amount of necrotic core in culprit coronary lesions than in patients without IR. Rather than a single measurement of IR index or each metabolic risk factor, clustering of metabolic risk factors for IR plays an important role in plaque vulnerability in patients with coronary artery disease. Our study demonstrates the role of IR on culprit coronary plaque and highlights the importance of the clustering of metabolic risk factors for IR in vulnerable plaque pathogenesis.